Late‐Onset Meningitis due to Serratia marcescens in a Preterm Infant: A Rare Sporadic Case Report From a Cambodian NICU - Bunngeth Seng; Sethikar Im; Sakviseth Bin (Clinical Case Reports, 2026)
ABSTRACT Late‐onset neonatal meningitis due to Serratia marcescens is an uncommon but potentially life‐threatening healthcare‐associated infection in NICUs. We report a sporadic case in a preterm infant who developed fever on Day 17 of life after a prolonged hospital stay for feeding difficulties and neonatal jaundice. Sepsis workup confirmed the diagnosis with S. marcescens in both blood and cerebrospinal fluid. Serial lumbar punctures confirmed progressive improvement in cerebrospinal fluid parameters and sterilization of cultures, after a 21‐day course of meropenem with 7 days of amikacin. The infant was discharged without neurological complications. This case highlights the importance of early recognition of late‐onset neonatal meningitis, appropriate broad‐spectrum antimicrobial therapy, and serial lumbar punctures to guide treatment and optimize outcomes in gram‐negative neonatal meningitis.